Comparative analysis of fatty acid profile in commercially available Greek Cheeses - Elisavet Giamouri; Panagiota Kyriakaki; Eleni C. Pappa; Efthymia Kondyli; Lida Papalamprou; Michael Goliomytis; Athanasios C. Pappas; Constantinos A. Georgiou; Eleni Tsiplakou (International Dairy Journal, 2026)

Seasonal and diel activity patterns of the Balkan chamois in Greece: first insights from camera trap data - Konstantinos Papakostas; Haritakis Papaioannou; Athanasios Gerogiannis; Athanasios Korakis; Anastasios Pappas; Vassiliki Kati (Mammal Research, 2026)
This study presents the first assessment of the activity patterns of the Balkan chamois ( Rupicapra rupicapra balcanica ) in Greece using camera traps, with a focus on potential differences between forested and open habitats. We deployed 49 camera traps across northwestern Greece (2015–2020), targeting areas with high chamois presence. Thirty-nine cameras yielded usable data (6,152 camera days). We analyzed seasonal and diel activity patterns based on independent photographic events. Chamois had a daily activity ranging from 9:00 to 21:00 and a peak at 11:00. The species used both forested and open areas, but we found no substantial differences in their activity patterns between the two. Nocturnal activity was generally low but increased during autumn in open areas, coinciding with the rutting season. We recommend a systematic camera trap deployment in future studies to evaluate activity overlap with sympatric species and the effects of human disturbance on chamois behavior.

Elemental profile of traditional, commercially available Greek cheeses - Eleni C. Pappa; Efthymia Kondyli; Athanasios C. Pappas; Lida Papalamprou; Andrea Mara; Panagiota Kyriakaki; Evangelos Zoidis; Agori Karageorgou; Elisavet Giamouri; Aikaterini Sarri; Panagiotis Simitzis; Michael Goliomytis; et al. (International Dairy Journal, 2025)

Cultivation of the macrophyte Lemna minor and the microalgae Chlorella sorokiniana in thermal mineral waters: Biomass characteristics, radioisotopes and heavy metals content - Alexandra Katsara; Eirini Zkeri; Maria Aloupi; Filothei K. Pappa; Christos Matsoukas; Athanasios S. Stasinakis (Environmental Pollution, 2024)

Influence of the Spatial Pressure Distribution of Breaking Wave Loading on the Dynamic Response of Wolf Rock Lighthouse - Darshana T. Dassanayake; Alessandro Antonini; Athanasios Pappas; Alison Raby; James Mark William Brownjohn; Dina D’Ayala (Journal of Marine Science and Engineering, 2021)
The survivability analysis of offshore rock lighthouses requires several assumptions of the pressure distribution due to the breaking wave loading (Raby et al. (2019), Antonini et al. (2019). Due to the peculiar bathymetries and topographies of rock pinnacles, there is no dedicated formula to properly quantify the loads induced by the breaking waves on offshore rock lighthouses. Wienke’s formula (Wienke and Oumeraci (2005) was used in this study to estimate the loads, even though it was not derived for breaking waves on offshore rock lighthouses, but rather for the breaking wave loading on offshore monopiles. However, a thorough sensitivity analysis of the effects of the assumed pressure distribution has never been performed. In this paper, by means of the Wolf Rock lighthouse distinct element model, we quantified the influence of the pressure distributions on the dynamic response of the lighthouse structure. Different pressure distributions were tested, while keeping the initial wave impact area and pressure integrated force unchanged, in order to quantify the effect of different pressure distribution patterns. The pressure distributions considered in this paper showed subtle differences in the overall dynamic structure responses; however, pressure distribution #3, based on published experimental data such as Tanimoto et al. (1986) and Zhou et al. (1991) gave the largest displacements. This scenario has a triangular pressure distribution with a peak at the centroid of the impact area, which then linearly decreases to zero at the top and bottom boundaries of the impact area. The azimuthal horizontal distribution was adopted from Wienke and Oumeraci’s work (2005). The main findings of this study will be of interest not only for the assessment of rock lighthouses but also for all the cylindrical structures built on rock pinnacles or rocky coastlines (with steep foreshore slopes) and exposed to harsh breaking wave loading.

Efficiency of alternative intensity measures for the seismic assessment of monolithic free-standing columns - Athanasios Pappas; Anastasios Sextos; Francesca da Porto; Claudio Modena (Bulletin of Earthquake Engineering, 2017)

Numerical analysis of the in-plane behaviour of three-leaf stone masonry panels consolidated with grout injection - Bruno Quelhas Silva; Athanasios Pappas; João Miranda Guedes; Francesca da Porto; Claudio Modena (Bulletin of Earthquake Engineering, 2017)

Influence of organic selenium supplementation on the accumulation of toxic and essential trace elements involved in the antioxidant system of chicken - Athanasios C. Pappas; Evangelos Zoidis; Constantinos A. Georgiou; Nikolaos Demiris; Peter F. Surai; Konstantinos Fegeros (Food Additives & Contaminants: Part A, 2011)